Factors affecting to the work-family conflict (wfc) among married female executive employees - Wijesingha, P.R.D. (University of Jaffna, 2019)
Work-family conflict is a common problem faced by employees in all sectors in the economy. Work-family conflict occurs when workplace responsibilities interfere with family life, such as inflexible working hours, work overload, interpersonal conflict at work and unsupportive supervisors in the organization that will leads to turnover intension. The purpose of this study is to identify the scenario of Work family conflict among married women (executive employees) in Business Process Management employees in Sri Lanka and identify some strategies to enhance the well-being of employees. Questionnaires and focused group interviews were used as the research instrument, and full time married female employees including HR & Training, Risk & Compliance, Legal Operations, Finance & Accounting Operations executive employees were taken as sample, with the time limitation researcher used 5 respondents for focus group interviews and 42 survey respondents based on convenient sampling method. The data were analyzed trough correlation and regression analysis in SPSS 21. According to the survey output, it is stated that the employees who are less than 35 of age dominating the industry. The finding shows the relationship between schedule control (time and workload), strain (burnout), and job satisfaction of the Work-family conflict of employees. According to the correlation and regression analysis output all the variables have positive relationship with WFC other than job satisfaction. This research has relevant implications for human resource managers/practitioners and future research suggestions are presented in this study.
Keywords: Work-family conflict; Business process management; Dual-earner couples; Job satisfaction; Strain; Structural control; Supervisors support